2019
DOI: 10.1124/dmd.119.086959
|View full text |Cite
|
Sign up to set email alerts
|

The Regional-Specific Relative and Absolute Expression of Gut Transporters in Adult Caucasians: A Meta-Analysis

Abstract: The aim of this study was to derive region-specific transporter expression data suitable for in vitro-to-in vivo extrapolation (IVIVE) within a physiologically based pharmacokinetic (PBPK) modeling framework. A meta-analysis was performed whereby literary sources reporting region-specific transporter expression obtained via absolute and relative quantification approaches were considered in healthy adult Caucasian individuals. Furthermore, intestinal total membrane protein yield was calculated to enable mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 67 publications
(108 reference statements)
1
34
1
Order By: Relevance
“…5A, left). Consistent with our data, Harwood et al showed that gene expression levels of PEPT1 in the human ileum were higher than those of other transporters (Harwood et al, 2019). As for the basolateral transporters, the proportions in the ileum were 41% (OSTβ), 30% (OSTα), 10% (MRP3), 9% (MRP1), and 7% (MRP5) (Fig.…”
Section: Expression Analysis Of Drug Transporters In the Intestinal Tsupporting
confidence: 91%
“…5A, left). Consistent with our data, Harwood et al showed that gene expression levels of PEPT1 in the human ileum were higher than those of other transporters (Harwood et al, 2019). As for the basolateral transporters, the proportions in the ileum were 41% (OSTβ), 30% (OSTα), 10% (MRP3), 9% (MRP1), and 7% (MRP5) (Fig.…”
Section: Expression Analysis Of Drug Transporters In the Intestinal Tsupporting
confidence: 91%
“…In previous targeted proteomic studies, quantifying OATP1A2 above limits of quantification was challenging in intestinal samples Drozdzik et al, 2014;Nakamura et al, 2016). A recent meta-analysis assessing relative and absolute regional expression of transporters in the intestine highlighted the challenges for assigning OATP1A2 expression directly into PBPK models in which a mechanistic intestinal model is described (Harwood et al, 2019). In this study, however, the abundance of OATP1A2 in all 16 samples was found to be above the limit of quantification at relatively similar levels to OST-a and OST-b.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to make meaningful progress toward achieving accurate PBPK predictions of absorption and gut wall clearance of orally administered drugs from the small intestine, it is vital that the abundance of DMEs and drug transporters and their variations are quantified in the small intestine. To capture the variability in a population, quantification of these protein abundances should be achieved in a sufficient number of individuals across different patient populations (Drozdzik et al, 2018;Harwood et al, 2019). The invasive nature of procedures and limited access to dedicated intestinal tissue banks has so far precluded such a large-scale study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…M-III focused on capturing rosuvastatin's delayed absorption, and the authors explained that while the distribution of BCRP (higher in the duodenum and jejunum) could cause the delay, a clinical genotyping study of subjects with reduced BCRP activity did not shift the t max as would have been expected 33 . The authors then postulated that basolateral transport by OST /ß 28 may explain the α absorption delay if OST /ß is highly expressed in the middle to terminal sections of the ileum α (however a recent meta-analysis found the regional expression for OST /ß to be more uniform 34 ). Mα III input a gut apical uptake CL int,T which was "model fit".…”
Section: Accepted Articlementioning
confidence: 99%